Experimental and numerical analysis of innovative processes for producing a resorbable cheekbone prosthesis. (October 2021) - Guglielmi, P.; Cusanno, A.; Bagudanch, I.; Centeno, G.; Ferrer, I.; Garcia-Romeu, M.L.; Palumbo, G.
Abstract: Magnesium alloys have gained interest in biomedical applications due to the mechanical properties (very similar to the human bones) and the capability to be absorbed (additional surgery steps after the implantation not necessary). But suitable manufacturing techniques are required for these alloys, since the standard ones (machining, casting) or even the newest (additive) cannot be successfully adopted in every situation or cannot guarantee the requirements in terms of precision or cost. In the present paper two sheet forming processes (the Super Plastic Forming and the Incremental Sheet Forming) have been investigated for manufacturing a resorbable cheekbone implant using the Mg alloy AZ31B. An experimental/numerical approach was adopted: specific tests were conducted for determining the material behaviour to be implemented in the process simulations used for designing both the manufacturing processes; finally some prototypes of the investigated case study were produced and the post forming characteristics (thickness, roughness, accuracy) evaluated. Both the processes allowed to successfully and optimally produce the resorbable prosthesis adopted as case study, which revealed to be characterised by good enough surface quality (especially in the case of the Super Plastic Forming) and uniform thickness distribution (especially in the case of the Incremental Sheet Forming).